Performance of Asphalt Mixture with Asbuton Based on Marshall Characteristics Compacted at Hot and Cold Temperatures - I Dewa Made Alit Karyawan; Ratna Yuniarti; Desi Widianty; Hasyim Hasyim; Mudji Wahyudi (Postgraduate, University of Mataram, 2021)
The use of natural asphalt is an alternative to meet the high demand for oil asphalt. Asbuton is natural asphalt from Buton Island, Indonesia. However, the use of Asbuton is not as easy as oil asphalt because the asphalt it contains is hard. The asphalt-concrete mixture must go through a rejuvenation process for several days before being compacted. This study aims to determine the performance of asphalt-concrete mixture using Asbuton if it is compacted immediately after mixing, without giving time for the rejuvenation process. Compaction is done when the mixture is hot and after the mixture is cold. Compaction of the asphalt-concrete mixture in hot temperature (150ÂºC), based on mechanical characteristics (stability, flow, and Marshall Quotient), has better performance than that compacted in cold temperature (30ÂºC). However, compaction in both hot and cold temperatures, based on their volumetric characteristics, does not meet the requirements for use as road pavements. The performance of the asphalt mixture can be improved by giving time in the process of softening the asphalt content in Asbuton